Antibody-Targeted Lethal Photosensitization of Porphyromonas gingivalis - Bhatti, M. (American Society for Microbiology, 2000)
We have previously demonstrated that Porphyromonas gingivalis is susceptible to killing by toluidine blue O (TBO) when irradiated with light from a helium-neon (HeNe) laser. The aim of this study was to determine whether a TBO-antibody conjugate (Ab-TBO) could be used to specifically target P. gingivalis to lethal photosensitization in the presence of Streptococcus sanguis or human gingival fibroblasts (HGFs). When a mixture of P. gingivalis and S. sanguis was exposed to 4 μg of TBO/ml and irradiated with HeNe laser light, there were 1.5- and 4.0-log(10)-unit reductions in the viable counts, respectively. In contrast, when TBO was conjugated with a murine monoclonal antibody against P. gingivalis lipopolysaccharide, the reductions in viable counts of P. gingivalis and S. sanguis amounted to 5.0 and 0.1 log(10) units, respectively. Lethal photosensitization of P. gingivalis in the presence of HGFs using unconjugated TBO resulted in a 0.7-log(10)-unit reduction in P. gingivalis viable counts and a 99% reduction in the incorporation of tritiated thymidine ([(3)H]Tdr) by the HGFs. In contrast, when the Ab-TBO conjugate was used, there was a 100% reduction in P. gingivalis viable counts but no significant reduction in the incorporation of [(3)H]Tdr by HGFs. These results demonstrate that specific targeting of P. gingivalis can be achieved using TBO conjugated to a monoclonal antibody raised against a cell surface component of this organism.